Energy efficiency study in FTMSK building of Universiti Teknologi MARA Shah Alam / Mohd Nizar Mohd Nasir - Mohd Nasir, Mohd Nizar (2001)
People nowadays are more concerned about energy efficiency and conservation. One of the focal point is on the energy consumption in buildings. Energy audit is considered as one of the comprehensive methods in the checking the energy usage and wastage in building [1].This paper describes the actual implementation and the process of energy audit program at the Faculty of Information Technology and Quantitative Science(FTMSK), Universiti Teknologi MARA building.